The Validity of Authentic Deeds for Mortgage Loan Agreements in Banks When the Signing of the Contract Is Not Conducted Before a Notary/Ppat - Hirwansyah, Hirwansyah; Dodi Rusmana, Dodi Rusmana; Mohamad Ali Syaifudin, Mohamad Ali Syaifudin (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The Mortgage Loan Agreement (Kredit Pemilikan Rumah/KPR) in Indonesia is one of the central components in banking financing activities, which carries substantial economic and commercial value. Within the KPR process, the use of an authentic deed is indispensable. The validity of an authentic KPR deed signed without the presence of a Notary/PPAT constitutes a violation of the professional code of ethics and an unlawful act. This journal research employs a normative legal research method, which positions law as a structure and system of norms, using primary legal materials such as statutes and regulations, secondary materials such as books and journals, and tertiary materials including manuals and explanatory documents related to the primary and secondary sources. The findings show that a KPR deed signed without the Notary’s presence loses its authentic character and is downgraded to a private deed, thereby losing its perfect evidentiary value (volledig bewijs). This condition weakens the legal position of the bank as creditor in collection and collateral execution, increases the risk of disputes with debtors, and reduces legal certainty for all related parties. A Notary/PPAT who fails to ensure compliance with formal procedures may be held civilly liable based on Articles 1365 and 1366 of the Indonesian Civil Code and may also face ethical sanctions from the Notary Honorary Council (DKN) and the Notary Honorary Assembly (MKN). Professionalism of the Notary/PPAT in performing their duties is crucial to maintaining the legal legitimacy of KPR deeds and protecting the interests of both creditors and debtors.